Mineral and Trace Metal Levels of Akçakatik Cheese Collected from Mediterranean Region-Turkey - Kirdar, S.S.; Ocak, E.; Köse, S. (Asian Journal of Chemistry, 2012)
In this study, 15 randomly selected samples of Akçakatik, cheese were purchased from different markets in Mediterranean region of Turkey. Mineral, trace and heavy metals including calcium, potassium, magnesium, copper, manganese, iron and zinc were analyzed using atomic absorption spectrometry. The ash content was in the range 4.89-8.53 %. The mean concentration of 49.62, 417.74 and 2842.24 mg/kg was measured for Mg, K and Ca, respectively. The concentration of the tested metals was in the range Zn > Fe > Mn > Cu. The mean concentration of 3.36, 6.15, 12.62 and 13.92 mg/kg was measured for Cu, Mn, Fe and Zn, respectively. In our samples, tested levels were higher than reported in previous studies, except the elements Fe and Ca.